Possibilities of using wastewater in sewage treatment plants as a source of heat - Szaflik, Władysław (Instal, 2022)
Preventing climate change is a priority for the European Union. In order to reduce CO2 emissions into the atmosphere and thus the negative impact of human activity on the environment, the European Parliament and the Council of the European Union have developed and enacted a number of directives. Improving the energy efficiency of systems used by people is a priority task included in the European Union policy. Energy obtained from the combustion of biogas and sewage sludge is widely used at wastewater treatment plants, while the heat recovered from wastewater is used only to a small extent. The article presents methods of heat recovery from wastewater and possibility of its application at wastewater treatment plants. The heat contained in the wastewater is discharged into the sewage system and further into the wastewater treatment plant. In most wastewater treatment plants in Poland, the heat is not utilized and flows with the treated wastewater to the reception tank. The lack of utilization of this heat is due to the low temperature of the wastewater, which is higher than the temperature of cold water supplied to buildings by only a few to several degrees Celsius. This limits the direct use of the heat contained in them with heat exchangers. In wastewater treatment plants, the higher temperature heat is used for heating, hot water preparation and technological needs. A higher temperature of the heated medium than in heat exchangers may be obtained with heat pumps, where wastewater can be used as lower heat source. Unfortunately, this temperature cannot be too high as the efficiency of heat pumps (COP) decreases with the increase of the temperature in the condenser. The basis of any analysis of the possibility of using heat from wastewater is the determination of its temperature. The analysis is based on the example of the Zdroje Wastewater Treatment Plant in Szczecin, for which the results of wastewater temperature measurements are presented for individual days in 2020. Analysis was also performed for water taken at the Miedwie intake, which feeds the wastewater treatment plant’s inflow areas, and for the average daily outdoor air temperature. The average daily efficiency of heat extraction with heat pumps from sewage at the plant and from outdoor air was determined for selected months. The efficiency of heat extraction depends on the temperature of the lower and upper heat source. The paper presents the results of performance calculations when the lower heat sources are wastewater and outside air. The efficiency of heat extraction from wastewater is higher than that of heat extraction from air. The relative increase in pump efficiency was also determined when wastewater is the lower heat source instead of the outside air.
Keywords: wastewater treatment; wastewater heat recovery; wastewater treatment plant heat management